Multicultural Education and the Strengthening of Character Education in the Indonesian Context - Syofrianisda Syofrianisda; Suriyati Suriyati; Wahyu Priyanti; Julhadi Julhadi (Hikmah, 2025)
Indonesia, as a pluralistic nation, faces serious challenges in the form of increasing intolerance, identity-based conflicts, and the weakening of national character values. This condition indicates that education has not yet fully functioned as a means of managing diversity as a social strength. This study aims to analyze the concept of multicultural education within the social, cultural, and historical context of Indonesia and examine its relevance to strengthening character education. The research employs a qualitative approach using library research methods through critical analysis of scholarly literature, expert perspectives, and relevant educational policy documents. The findings reveal that multicultural education plays a strategic role as an educational paradigm that emphasizes equality, respect for differences, and social justice, and serves as a foundational framework for strengthening character education grounded in the Indonesian context. The integration of multicultural education and character education is shown to foster tolerant, empathetic, and democratic attitudes among students. The implications of this study highlight the importance of mainstreaming multicultural education within curricula, school culture, and national education policies to develop an inclusive and civilized national character.